Manajemen Rantai Pasok Berkelanjutan Sebagai Keunggulan Kompetitif Perusahaan - Bernardino Wan Jul Tri Berkat Gulo (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Amidst growing environmental awareness and social demands, Sustainable Supply Chain Management (SSCM) has shifted from a mere moral obligation to a core strategy for competitive advantage. This paper analyzes how integrating economic, environmental, and social aspects into the supply chain can create added value for companies. Using the Triple Bottom Line framework, the study concludes that companies implementing sustainable supply chains are able to reduce operational costs, enhance brand image, and mitigate regulatory risks, ultimately creating a competitive advantage that is difficult for competitors to imitate.